Challenges and trends of Blockchain Interoperability and multi-blockchain architectures - Silva, Pedro M. R. G.; Silva, Matheus Lázaro Honório da; Velasco, Gislainy; Carvalho, Sergio T. (Anais da Escola Regional de Informática de Goiás (ERI-GO), 2025)
The blockchain landscape in healthcare has undergone significant transformations, transitioning from large public networks to customizable and private blockchains, raising questions about how to integrate multiple blockchains into a unified system. This paper examines emerging trends and persistent challenges in blockchain interoperability within healthcare datasharing systems. We investigate solutions including Polkadot, Hyperledger Cacti, and Cosmos, revealing gaps: the absence of general protocols for heterogeneous blockchain communication, reliance on external trust rather than cryptographic consensus in multi-chain transactions, and inadequate identity verification mechanisms. We identify Self-Sovereign Identity (SSI) and Decentralized Identifiers (DIDs) as promising approaches for the identity challenge, and multi-blockchain consensus protocols as an unexplored solution where nodes from multiple chains collaboratively validate cross-chain transactions.